Immune responses to peptides containing homocitrulline or citrulline in the DR4-transgenic mouse model of rheumatoid arthritis. (May 2018) - Lac, Patrick; Saunders, Sheri; Tutunea-Fatan, Elena; Barra, Lillian; Bell, David A.; Cairns, Ewa
Abstract: Antibodies to proteins/peptides containing citrulline are hallmarks of Rheumatoid Arthritis (RA). These antibodies are strongly associated with the expression of the Shared Epitope (SE). RA patients also generate antibodies to homocitrulline-containing proteins/peptides (also referred to as anti-carbamylated protein antibodies (Anti-CarP)). This study was undertaken to investigate the relationship between homocitrulline and citrulline immune responses using an established mouse model of RA: DR4-transgenic (DR4tg) mice that express the human SE. C57BL/6 (B6) and DR4tg (on a B6 background) mice were immunized subcutaneously with a homocitrullinated peptide (HomoCitJED). Splenic T cell proliferation was evaluated by 3 H-thymidine incorporation assay. Antibodies to homocitrullinated and citrullinated antigens were screened by enzyme-linked immunosorbent assay (ELISA). Antibody cross-reactivity was examined by inhibition with HomoCitJED and its citrullinated counterpart peptide, CitJED (the number of homocitrullines in HomoCitJED is equal to the number of citrullines in CitJED). HomoCitJED-immunized DR4tg mice developed early T and B cell responses to HomoCitJED and late responses to CitJED. These mice also developed anti-CCP2 antibodies. In some mice, antibodies to HomoCitJED were also reactive to CitJED. B6 mice immunized with HomoCitJED developed late T and B cell responses to HomoCitJED, but did not generate responses to citrullinated antigens. Unlike DR4tg mice, anti-HomoCitJED antibodies from B6 mice did not react to CitJED. In conclusion, DR4tg mice immunized with HomoCitJED developed immune responses to CitJED, indicating cross-reactivity. CitJED immune responses were dependent on the SE. HomoCitJED responses occurred in the absence of the SE (B6 mice); however, they developed earlier in DR4tg SE-expressing mice. Highlights: Homocitrullinated peptide-immunized DR4tg mice that express the Shared Epitope develop immune responses to homocitrulline. Anti-homocitrulline, but not anti-citrulline immune responses can occur in the absence of the Shared Epitope. Antibodies from homocitrullinated peptide-immunized DR4tg mice are cross-reactive to homocitrulline and citrulline.